Peningkatan Hasil Belajar IPAS Menggunakan Model Cooperative Learning tipe Jigsaw Peserta Didik Kelas IV SDS IT Luqman Kota Padang - Aisyah, Siti; Zuryanty; Fitria, Yanti; Rahmi, Gita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted because the learning outcomes of students in the subject of science in grade IV of SDS IT Luqman Padang City are still low. The purpose of the research is to improve the learning outcomes of students in science using the jigsaw cooperative learning model in the learning process. The research used a type of classroom action research carried out in 2 learning cycles involving 22 grade IV students. The research used data collection techniques through observation, giving tests, and documentation. The results of the study showed an increase in student learning outcomes in aspects of attitudes, knowledge, and skills. Improvements also showed in teacher activities, student activities, and the quality of learning planning. Therefore, through the jigsaw cooperative learning model is considered capable of helping improve students' science learning outcomes.